2000
DOI: 10.1524/zpch.2000.214.6.823
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Regularities in the Behaviour of the Critical Constants of Fluid Alkali Metals

Abstract: We report new measurements of the densities of the coexisting liquid and vapour phases of the alkali metals K and Na. Comparison of the coexistence curve of K with those of Cs and Rb in reduced form shows that the alkali metals behave very similarly close to the critical temperatures. The experimental values of the critical constants T

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…On the other hand, the experimentally observed coexistence curves for liquid alkali metals, such as K, Rb, Cs, etc., display quite different behavior from that of SF 6 [13,14]. These metals exhibit marked deviations from the Law of the Rectilinear Diameter with a smooth downward curvature extending over quite a wide range of temperature even below T ≃ 0.9 T c ; but they do not show a sharply dropping singularity near criticality as seen for SF 6 : see Fig.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…On the other hand, the experimentally observed coexistence curves for liquid alkali metals, such as K, Rb, Cs, etc., display quite different behavior from that of SF 6 [13,14]. These metals exhibit marked deviations from the Law of the Rectilinear Diameter with a smooth downward curvature extending over quite a wide range of temperature even below T ≃ 0.9 T c ; but they do not show a sharply dropping singularity near criticality as seen for SF 6 : see Fig.…”
Section: Introductionmentioning
confidence: 84%
“…Deviations from the Law of the Rectilinear Diameter have indeed been observed in several careful experiments on various fluids [11,12,13,14,15,16]. Among these, the seminal study of SF 6 by Weiner et al [12] more than 30 years ago reported a surprisingly sharp and abrupt singular downturn of the diameter very close to T c .…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…We then apply the finite temperature aiGEMC method to compute the liquid-vapor equilibrium of sodium for which several experimental data sets are available. [33][34][35] The critical densities and temperatures range from 0.175 to 0.3 g cm À3 in density and from 2485 to 2573 K in temperature. The sodium vapor is mainly an atomic gas without large clusters, 36 which thus greatly simplifies the structural constraints.…”
Section: Introductionmentioning
confidence: 99%
“…The possibilities of experimental research are also limited. Due to the difficulty of conducting experiments at high temperatures, the critical point and binodal parameters were obtained only for a small amount of substances, which include alkali metals and mercury, which have relatively low temperature characteristics [6][7][8][9][10][11]. For other materials, there are only theoretical estimates within the framework of various models, among which phenomenological methods [12][13][14][15][16][17][18][19][20][21][22][23][24] and atomistic modeling methods [25][26][27][28][29][30][31] stand out.…”
Section: Introductionmentioning
confidence: 99%